2018
DOI: 10.21595/jve.2017.18647
|View full text |Cite|
|
Sign up to set email alerts
|

Monitoring of blast-induced ground vibration using WSN and prediction with an ANN approach of ACC dungri limestone mine, India

Abstract: Blast-induced ground vibration (BIGV) is an undesirable environmental issue in and around mines. Usage of a high amount of explosive causes ground vibrations that are harmful to the nearby habitats and dwellings. In this paper, an attempt has been made to monitor the BIGV with low-cost wireless sensor network (WSN) and prediction of peak particle velocity (PPV) using an artificial neural network (ANN) technique at ACC Dungri limestone mine, Bargarh, Odisha, India. Eleven blasts PPV were recorded at different l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In 2018, Ragam and Nimaje have designed and developed a WSN blast-induced vibration monitoring system includes ADXL 345 accelerometer and ZigBee as RF module. The prototype was installed along with minimate plus seismograph at ACC Dungri limestone mine, India [20]. The authors [13][14][15][16][17][18][19][20] implemented a WSN system using RF modules such as ZigBee and ChipCon 2420 chip only.…”
Section: Previous Workmentioning
confidence: 99%
“…In 2018, Ragam and Nimaje have designed and developed a WSN blast-induced vibration monitoring system includes ADXL 345 accelerometer and ZigBee as RF module. The prototype was installed along with minimate plus seismograph at ACC Dungri limestone mine, India [20]. The authors [13][14][15][16][17][18][19][20] implemented a WSN system using RF modules such as ZigBee and ChipCon 2420 chip only.…”
Section: Previous Workmentioning
confidence: 99%
“…Ragam and Nimaje evaluated the blast-induced ground vibration at different mines using MLPNN technique along with statistical predictor models to predict the PPV. The results were shown that the developed ANN gives more accurate prediction compare to other models [19][20] . Other researchers predicted PPV based on ANN models in different projects and found very superior results compared with conventional methods.…”
Section: Introductionmentioning
confidence: 95%
“…Few researchers were developed artificial neural network (ANN) models to predict the PPVin opencast mines. [9][10][11][12][13][14] Other researchers were predicted PPV based on various novel soft computing technique approaches such as artificial neural adoptive neuro fuzzy interference system (ANFIS), Gene Expression Programming (G EP), fuzzy interface systems (FIS), genetic algorithm (GA), support vector machine (SVM), group method of data handling (GMDH), particle swarm optimization (PSO), imperialist competitive algorithm (ICA), hybrid models including PSO-ANN, ICA-ANN in multiple projects and found very superior results compared to conventional predictor equations (see Table 2). The motto of the current study is to evaluate and estimate of ambiguous PPV by blasting process in Mine-A, India based on hybrid ensemble machine learning approach such as XGBoost-RF and Decision Tree, respectively.…”
Section: Previous Work(s)mentioning
confidence: 99%